Canopy structure and its relationship with yield and synchrony in pod maturity of mungbean (Vigna rediata L.) (Bangladesh Journal of Botany, 2020)
Field experiments were conducted under sub-tropical condition during March-May of two consecutive years of 2013 and 2014 to assess the effect of different levels of debranching and spacing on synchronous pod ripening and yield of mungbean. The debranching levels were: (i) Category 1 [main stem (MS) with 4 branches per plant, control], (ii) category 2 (MS with three branches per plant), (iii) category 3 (MS with two branches per plant), (iv) category 4 (MS with one branch per plant) and (v) category 5 (only MS). Under recommended plant spacing (30 cm × 10 cm), plants having MS with 3 branches produced the highest seed yield due to increased number of seeds per pod over category 1. The lowest seed yield was recorded in category 5 (only MS plant) due to fewer number of pods per plant. When the optimum plant population per unit area according to canopy area was considered, it was estimated that the highest plants/m2 was accommodated in MS only of 50 plants/m2 showing the highest seed yield (2570 kg/ha) followed by MS with one branch (40 plants/m2, 2460 kg/ha) and these two treatments also showed synchronous pod maturity. The lowest plant population per unit area was accommodated in MS with 3 and 4 branches (25 plants/m2) and also showed lower seed yield (1910 and 1940 kg/ha, respectively) behaving asynchronous pod maturity.